Educational project “Mathematics for secondary education (MATEM)”, your academic task during the year 2012: participants´ perspective - Alfaro Arce, Ana Lucía (2014)
"MATEM" is a university outreach project. Among its objectives is to improve the mathematics education at the high school level and to accomplish it public universities work together with high school´s teachers and students. The study´s aim was to research various aspects of MATEM Project to order to evaluate its development and consider recommendations for making decisions. This paper summarizes the perceptions of high school students enrolled during 2012 in courses Precalculus and Calculus, moreover the opinion of mathematics teachers. The main results were that MATEM is an academic activity attractive for math teachers and student population from different regions of the country, although sometimes are not available the necessary conditions to develop it in their respective institutions, to have passed a university course, get more practice for the standard test at the end of high school, increase their math skills and prepare for college courses were the aspects that motivate students to enroll in the project, however the development of reasoning skills and abilities were more frequently pointed by respondents.